Modeling gross motor developmental curves of extremely and very preterm infants using the AIMS home-video method. (December 2022) - Suir, I.; Boonzaaijer, M.; Oudgenoeg-Paz, O.; Westers, P.; de Vries, L.S.; van der Net, J.; Nuysink, J.; Jongmans, M.J.
Abstract: Background: Motor development is one of the first signals to identify whether an infant is developing well. For very preterm (VPT) infants without severe perinatal complications, little is known about their motor developmental curves. Aims: Explore gross motor developmental curves from 3 until 18 months corrected age (CA) of VPT infants, and related factors. Explore whether separate profiles can be distinguished and compare these to profiles of Dutch term-born infants. Study design: Prospective cohort study with parents repeatedly recording their infant, using the Alberta Infant Motor Scale (AIMS) home-video method, from 3 to 18 months CA. Subjects: Forty-two Dutch infants born ≤32.0 weeks gestational age and/or with a birthweight (BW) of <1500 g without severe perinatal complications. Outcome measures: Gross motor development measured with the AIMS. Results: In total 208 assessments were analyzed, with 27 infants ≥five assessments, 12 with <four, and three with one assessment. Sigmoid-shaped gross motor curves show unidirectional growth and variability. No infant or parental factors significantly influenced motor development, although a trend was seen for the model where lower BW, five-minute Apgar score <7, and Dutch native-speaking parents were associated with slower motor development. Three motor developmental profiles of VPT infants were identified, early developers, gradual developers, and late bloomers, which until 12 months CA are comparable in shape and speed to profiles of Dutch term-born infants. Conclusions: VPT infants show great intra- and interindividual variability in gross motor development, with three motor profiles being distinguished. From 12 months CA onwards, VPT infants appear to develop at a slower pace. With some caution, classifying infants into motor developmental profiles may assist clinical decision-making. Highlights: VPT infants without severe perinatal complications show intra- and interindividual variability in gross motor development. This variability seems to be captured well by three distinguishable profiles. VPT early developers seem to develop at the same pace as TB early developers. VPT gradual developers and late bloomers decrease in developmental pace from 12 months onwards. Birthweight, five-minute Apgar score, and parental Dutch mother tongue may be associated with a slower motor development.